KOMPETENSI PEDAGOGIK GURU DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN MENGOPERASIKAN APLIKASI PERANGKAT LUNAK - KARTIKASARI, Hanum (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
The objectives of this research are to investigate: (1) the effect of the teacher?s pedagogical competency on the learning achievement in Operating-the-Software-Application subject matter of the students of the Department of Office Administration of State Vocational High School 1 of Surakarta in Academic Year 2012/2013; (2) the effect of the learning facility on the learning achievement in Operating-the-Software-Application subject matter of the students of the Department of Office Administration of State Vocational High School 1 of Surakarta in Academic Year 2012/2013; and (3) the simultaneous effect of the teacher?s pedagogical competency and the learning facility on the learning achievement in Operating-the-Software-Application subject matter of the students of the Department of Office Administration of State Vocational High School 1 of Surakarta in Academic Year 2012/2013. This research used the descriptive quantitative research method. The population of the research of the students in Grades XI and XII as many as 150. The samples of the research were 108 students. The samples were taken by using the stratified random sampling technique based on the table of Krejcie-Morgan with the error level of 5 %. The data of the research were gathered through questionnaire and documentation. They were then analyzed by using the multiple linear regression analysis aided by the computer program of SPSS 17.The results of the research are as follows: (1) there is a significant effect of the teacher?s pedagogical competency on the learning achievement in Operating-the-Software-Application subject matter of the students of the Department of Office Administration of State Vocational High School 1 of Surakarta in Academic Year 2012-2013 as indicated by the value of rcount= 0.443 > that of rtable = 0.187; (2) there is a significant effect of the learning facility on the learning achievement in Operating-the-Software-Application subject matter of the students of the Department of Office Administration of State Vocational High School 1 of Surakarta in Academic Year 2012-2013; as shown by the value of rcount = 0.427> rtable = 0.187); and (3) there is a simultaneously significant effect of the teacher?s pedagogical competency and the learning facility on the learning achievement in Operating-the-Software-Application subject matter of the students of the Department of Office Administration of State Vocational High School 1 of Surakarta in Academic Year 2012-2013 as pointed out by the value of Fcount = 24.736 >Ftable = 3.083 Keywords: Teacher?s pedagogical competency, learning facility, learning achievement, and software application.